2016
DOI: 10.7150/ijbs.15943
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 in tumor-associated macrophages promotes metastatic potential of breast cancer cells through Akt pathway

Abstract: Tumor-associated macrophages (TAMs) promote cancer development and progression by releasing various cytokines and chemokines. Previously, we have found that the number of COX-2+ TAMs was associated with lymph node metastasis in breast cancer. However, the mechanism remains enigmatic. In this study, we show that COX-2 in breast TAMs enhances the metastatic potential of breast cancer cells. COX-2 in TAMs induces MMP-9 expression and promotes epithelial-mesenchymal transition (EMT) in breast cancer cells. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 56 publications
(62 reference statements)
2
49
0
Order By: Relevance
“…For example, COX‐2 inhibitors also suppress tumor immune evasion by inhibiting M2 macrophages and T regulatory cells 41,42 . Cyclooxygenase‐2 in tumor‐associated macrophages (TAMs) promotes breast cancer metastasis through the induction of MMP9 and the promotion of EMT in tumor cells 43 . In addition, cancer‐associated fibroblasts (CAFs) are major sources of COX‐2/PGE 2 in the tumor microenvironment 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, COX‐2 inhibitors also suppress tumor immune evasion by inhibiting M2 macrophages and T regulatory cells 41,42 . Cyclooxygenase‐2 in tumor‐associated macrophages (TAMs) promotes breast cancer metastasis through the induction of MMP9 and the promotion of EMT in tumor cells 43 . In addition, cancer‐associated fibroblasts (CAFs) are major sources of COX‐2/PGE 2 in the tumor microenvironment 44 .…”
Section: Discussionmentioning
confidence: 99%
“…As it has been discussed, NF‐κβ is a transactivator for COX‐2 promoter contributed to activation of COX‐2 in both cancer cells (Charalambous et al, ) and TAMs (Hung et al, ). There is also evidence for protumoral activity of COX‐2 in macrophages (Lu Gan et al, ). Taken together, it could be speculated that macrophage polarity is not influenced by COX‐2.…”
Section: Contribution Of Cox‐2‐expressing Tumor‐associated Macrophagementioning
confidence: 99%
“…Recently, it has been reported that cyclooxygenase 2 (COX-2) and prostaglandin E2 (PGE2) regulate cancer progression and metastasis [ 5 , 6 ]. Overexpression of COX-2 in tumor-associated macrophages promotes pro-metastatic effects of breast cancer cells by regulating MMP-9 and EMT and Akt pathway, and the COX-2/PGE2 axis mediates cell invasion in EGF-induced ovarian cancer [ 7 , 8 ]. Especially, PGE2 produced by inducible COX-2 and mPGES-1 promotes cancer cell proliferation in vitro and in vivo , and induced EMT in prostate cancer [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%